Exposure to Inactivated Deformed Wing Virus Leads to Trans-Generational Costs but Not Immune Priming in Honeybees (Apis mellifera) - Leponiemi, Matti; Amdam, Gro V.; Freitak, Dalial (Frontiers in Ecology and Evolution, 2021)
Pathogens are identified as one of the major drivers behind the honeybee colony losses, as well as one of the reasons for the reported declines in terrestrial insect abundances in recent decades. To fight infections, animals rely on their immune system. The immune system of many invertebrates can be primed by exposure to a pathogen, so that upon further exposure the animal is better protected. The protective priming effect can even extend to the next generation, but the species capable of priming the immune system of their offspring are still being investigated. Here we studied whether honeybees could prime their offspring against a viral pathogen, by challenging honeybee queens orally with an inactivated deformed wing virus (DWV), one of the most devastating honeybee viruses. The offspring were then infected by viral injection. The effects of immune priming were assayed by measuring viral loads and two typical symptoms of the virus, pupal mortality, and abnormal wing phenotype. We saw a low amount of wing deformities and low pupal mortality. While no clear priming effect against the virus was seen, we found that the maternal immune challenge, when combined with the stress caused by an injection during development, manifested in costs in the offspring, leading to an increased number of deformed wings.